2016
DOI: 10.1108/pr-02-2015-0024
|View full text |Cite
|
Sign up to set email alerts
|

Rewarding employees in turbulent economies for improved organisational performance

Abstract: Structured AbstractPurpose: This study explores the application of total reward practices in small and mediumsized enterprises (SMEs) in the South-Eastern European (SEE) region and the reward elements positively affecting organisational performance.Design/Methodology/Approach: The sample consists of 199 SMEs operating in SEE countries which are either under economic crisis or transition: Greece, Bulgaria, Romania, Albania, Kosovo and the Former Yugoslav Republic of Macedonia (FYROM).Findings: SMEs in the SEE r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 68 publications
5
36
0
Order By: Relevance
“…The front-line managers were offering employees additional days off and allowing them to leave work early. This finding supports Prouska et al [90] who found that work-life balance motivates employees to work harder because it is perceived as a reward. In contrast, Peluso et al [91] conducted a quantitative research and concluded that while many employees like to be rewarded, whether in monetary or non-monetary form, it differs from one individual to another, wherein some individuals may not be motivated by the reward provided by the employers.…”
Section: Third Approach-rewarding the Employees In Exchange For Helping To Address The Personnel Resource Shortagessupporting
confidence: 87%
“…The front-line managers were offering employees additional days off and allowing them to leave work early. This finding supports Prouska et al [90] who found that work-life balance motivates employees to work harder because it is perceived as a reward. In contrast, Peluso et al [91] conducted a quantitative research and concluded that while many employees like to be rewarded, whether in monetary or non-monetary form, it differs from one individual to another, wherein some individuals may not be motivated by the reward provided by the employers.…”
Section: Third Approach-rewarding the Employees In Exchange For Helping To Address The Personnel Resource Shortagessupporting
confidence: 87%
“…Performance pressure, threat appraisal and work engagement Performance pressure is a subjective experience of "any factor or combination of factors that increase the importance of performing well" (Baumeister, 1984, p. 610). Rewards, punishments and competition in the workplace can produce the perception that meeting goals and achieving high levels of performance is highly important (Prouska et al, 2016), which is also referred to as performance pressure (Zhang et al, 2017). According to Gardner (2012), performance pressure is an external force imposed on employees to deliver a superior outcome and high levels of performance.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…Among the characteristics that distinguish turbulence from other critical situations are its large and uncontrollable scale, high velocity and fluctuation, its cascading effect and unclear patterns of evolution, leading to a chaotic situation (Prouska et al, 2016). Turbulence, broadly defined, "is a measure of change that occurs in the factors or components of an organization's environment.…”
Section: Turbulent Times As a Moderatormentioning
confidence: 99%